2014
DOI: 10.4269/ajtmh.14-0161
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes for Patients with Multidrug-Resistant Tuberculosis in Post-Earthquake Port-au-Prince, Haiti

Abstract: Abstract. We report outcomes and 12-month survival for the first cohort of patients to undergo multidrug-resistant tuberculosis (MDR-TB) treatment after the earthquake in Haiti. From March 3, 2010 to March 28, 2013, 110 patients initiated treatment of laboratory-confirmed MDR-TB at the Groupe Haïtien d'Etude du Sarcome de Kaposi et des Infections Opportunistes (GHESKIO) Center in Port-au-Prince, Haiti. Twenty-seven patients (25%) were human immunodeficiency virus (HIV)-positive. As of October 31, 2013, 95 (86%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…The finding of the current study is also consistent with those of previous studies [18][19][20], having shown that the risk of death among those who had HIV co-infection increased by two. This underscores the need to give priority attention to MDR-TB patients with HIV coinfection.…”
Section: Discussionsupporting
confidence: 93%
“…The finding of the current study is also consistent with those of previous studies [18][19][20], having shown that the risk of death among those who had HIV co-infection increased by two. This underscores the need to give priority attention to MDR-TB patients with HIV coinfection.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, these mutations were identified in two HIV coinfected patients who had a 100% smear conversion rate at 11 months and 8 months respectively (Table 1). This finding emphasizes the importance of prolonged RIF TB therapy for improved treatment outcome (15,16) . However previous studies have shown that smear microscopy is less sensitive in HIV positive patients with MDR-TB and cure should be confirmed after obtaining at least 5 negative sputum culture results during 12 months of treatment (6) .…”
Section: Discussionmentioning
confidence: 83%
“…There are several ongoing clinical trials examining such novel regimens. [41][42][43] Treatment outcomes for MDR-TB in Haiti are among the best in the world, 16,17 with the use of standard long-course therapy in conjunction with DST. The Haitian National TB Program is in the process of selecting a shorter course regimen that would lead to continued high success rates, without increasing toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite suffering a devastating earthquake in 2010, MDR-TB treatment outcomes have been excellent with cure rates as high as 88%. 16,17 Ethics. This study was approved by the institutional review boards of all affiliated institutions.…”
Section: Methodsmentioning
confidence: 99%